Association of obesity with vitamin D deficiency and the clinical implications - Oommen, Anitha; Al-Zahrani, Ibrahim Hassan (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is a complex disorder which leads to health problems like diabetes, hypertension and hyper cholesterolemia. It has been reported that obesity is associated with vitamin D insufficiency due to decreased bio-availability. The aim of the present study is to investigate whether vitamin D deficiency can be a causative factor for obesity in Saudi women above 40 years. Methods: 100 Saudi female patients above 40 years who came to the outpatient department of Arar central hospital were selected for the study. Patients who were on immunosuppressive drugs, with hormonal disorders and with impaired renal function were excluded from the study. The data was collected using a questionnaire which included the socio demographic details, height, weight and medical history and the serum vitamin D levels were assessed. Results: 69% of the Saudi women were obese (BMI >30). 84% (n=58) of the obese women had vitamin D deficiency (<50 nmols/l) while 69.6% of the overweight women had vitamin D deficiency. 43.5% (n = 30) of obese women had diabetes, 44.9% (n=31) of obese women had hypertension. The association between obesity and vitamin D deficiency was not significant. Conclusions: No significant association was found between obesity and vitamin D deficiency indicating that vitamin D deficiency has no significant role in causing obesity in Saudi women above 40 years.